Status dan Implikasi Tentara Bayaran Studi Kasus Legiun Georgia - Fransisca, Helsa Gita; Tri, Widya (Eastasouth Institute, 2024)
This article discusses related to the status and implications of mercenaries according to International Humanitarian Law focusing on the case study of the Georgia Legion. The goal is to examine the status and implications of the Georgia Legion mercenaries in international armed conflicts. Using the normative juridical method, namely by analyzing laws, principles, theories, and laws and regulations related to the status of mercenaries. The data acquisition refers to Article 47 of Additional Protocol I of the Geneva Convention of 1989. This article draws several conclusions, namely: first, mercenaries are not entitled to the status of combatants or prisoners of war under the Geneva Conventions, since their involvement in armed conflicts is aimed at obtaining personal gain. Second, the implications of the use of mercenaries are returned to the decisions of the countries of the parties to the conflict. In the case of the Georgia Legion, the execution of Russian prisoners of war was included in the violatione